High-entropy silicon carbide anti-oxidation coating of Ti3Al-based composite material fastener and preparation method of high-entropy silicon carbide anti-oxidation coating
By applying a high-entropy silicon carbide antioxidant coating on the surface of SiCf/Ti3Al composite fasteners, the problem of oxidation failure of the material at 800°C is solved, and higher oxidation resistance and low-temperature toughness are achieved.
Patent Information
- Application Number
- CN202411923443.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Due to insufficient Al content on the surface of SiCf/Ti3Al composite fasteners at 800°C, they cannot form a continuous and dense Al2O3 protective layer, resulting in severe oxidation and failure.
Using a high-entropy silicon carbide antioxidant coating, the introduction of a small amount of carbon and silicon vacancies in the high-entropy silicide promotes the outward diffusion of silicon, forming a dense and continuous SiO2 oxide layer, improving oxidation resistance and low-temperature toughness.
It effectively limits the inward diffusion of oxygen, improves oxidation resistance, and improves hardness and low-temperature toughness through carbon alloying, making the material more stable in service at high temperatures for a long time.
Smart Images

Figure CN119663184A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a high entropy silicon carbide anti-oxidation coating of a Ti3Al-based composite material fastener and a preparation method thereof. Background Art
[0002] Ti3Al alloy is an excellent high-temperature structural material in the temperature range of 600-700℃ due to its low density, high specific strength at high temperature and high-temperature creep resistance. It is widely used in the aerospace field. f The SiC / Ti3Al composite material has higher specific strength and specific stiffness and lower thermal expansion coefficient than the Ti3Al matrix, which further increases its service temperature to 800°C. It is more processable than ceramic-based high-temperature structural materials and is a candidate material for high-temperature fasteners for aerospace. However, at 800°C, SiC f Due to insufficient Al content, the surface of Ti3Al composite fasteners cannot form a continuous and dense Al2O3 protective layer, resulting in severe oxidation. In order to avoid the failure of Ti3Al-based composite fasteners that have been in service for a long time at 800℃ due to oxidation, improving their high-temperature oxidation resistance is an urgent problem to be solved.
[0003] The silicide coatings (MoSi2, etc.) in the prior art are widely used as high-temperature protective coatings due to their high melting point, good thermal stability and strong self-healing ability. Their excellent oxidation resistance is due to their high silicon content. During the oxidation process, Si is preferentially oxidized, and a continuous and dense SiO2 protective layer is easily formed, thereby preventing further inward diffusion of oxygen, thereby protecting the substrate from oxidation. However, the single binary silicide anti-oxidation coating still has the defects of poor oxidation resistance and poor low-temperature toughness, and further improvement is urgently needed to meet the service requirements of Ti3Al composite fasteners at high temperatures. Summary of the invention
[0004] The purpose of the present invention is to provide a high-entropy silicon carbide anti-oxidation coating for a Ti3Al-based composite fastener and a preparation method thereof. The present invention introduces a small amount of carbon and silicon vacancies into the high-entropy silicide to promote the outward diffusion of silicon during the oxidation process, thereby forming a dense and continuous SiO2 oxide layer on the alloy surface, thereby improving the oxidation resistance and low-temperature toughness.
[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:
[0006] A high entropy silicon carbide anti-oxidation coating, comprising metal elements and non-metal elements, wherein the metal elements include Ti, Zr, Nb, Mo and W, and the non-metal elements include Si and C;
[0007] The molar ratio of metal elements to non-metal elements is 1:1.5-2;
[0008] The molar ratio of Ti, Zr, Nb, Mo and W is 1-10:1-10:1-10:1-10:1-10;
[0009] The carbon atom content is 10-40% of the total number of high entropy silicon carbide atoms.
[0010] Preferably, the molar ratio of Si to C is 3:1-4.
[0011] Preferably, the thickness of the high entropy silicon carbide anti-oxidation coating is 2-5 μm.
[0012] The present invention also provides a method for preparing the high entropy silicon carbide anti-oxidation coating according to the above technical solution, comprising the following steps:
[0013] The target material is deposited on the surface of the substrate by magnetron sputtering to obtain the high entropy silicon carbide anti-oxidation coating on the surface of the substrate; the target material includes a mixture of TiSi2, ZrSi2, NbSi2, MoSi2, WSi2, WC and NbC.
[0014] Preferably, the substrate comprises a Ti3Al sheet or a Ti3Al-based composite material fastener.
[0015] Preferably, the target material installation method comprises: stacking and arranging from top to bottom in a vertical direction to form a first composite target and a second composite target; the arrangement order of the first composite target is TiSi2, ZrSi2, NbSi2, MoSi2 and WC, and the arrangement order of the second composite target is WC, MoSi2, NbSi2, ZrSi2 and TiSi2;
[0016] or the first composite targets are arranged in the order of TiSi2, ZrSi2, NbC, MoSi2 and WC, and the second composite targets are arranged in the order of WC, MoSi2, NbC, ZrSi2 and TiSi2;
[0017] The first composite target and the second composite target are arranged opposite to each other;
[0018] The arrangement period of the first composite target and the second composite target is independently 1 to 3.
[0019] Preferably, the parameters of the magnetron sputtering include: the sputtering current of each target is 500-900 mA, the sputtering voltage value is 400-600 V, the substrate bias is -50--200 V, the sample holder speed is 150-250 r / h, and the back pressure is less than 4×10 -4Pa, the working pressure is 0.5-1.1 Pa, the substrate temperature is 300-500° C., the sputtering time is 40-80 min, and the target-substrate distance is 6-10 cm; the magnetron sputtering is carried out in an argon atmosphere; the gas flow value of the argon is 50-70 sccm.
[0020] Preferably, the temperature of the substrate during the magnetron sputtering is 300-500°C.
[0021] The present invention also provides a high entropy silicon carbide anti-oxidation coating for a Ti3Al-based composite material fastener, comprising a Ti3Al-based composite material fastener and a high entropy silicon carbide anti-oxidation coating deposited on the surface of the Ti3Al-based composite material fastener;
[0022] The high entropy silicon carbide anti-oxidation coating is the high entropy silicon carbide anti-oxidation coating described in the above technical solution or the high entropy silicon carbide anti-oxidation coating prepared by the preparation method described in the above technical solution.
[0023] The present invention provides a high entropy silicon carbide anti-oxidation coating, comprising metal elements and non-metal elements, wherein the metal elements include Ti, Zr, Nb, Mo and W, and the non-metal elements include Si and C; wherein the molar ratio of the metal elements to the non-metal elements is 1:1.5-2; the molar ratio of the Ti, Zr, Nb, Mo and W is 1-10:1-10:1-10:1-10:1-10; and the carbon atom content is 10-40% of the total number of high entropy silicon carbide atoms. In the high entropy silicon carbide anti-oxidation coating of the present invention, the metal elements randomly occupy the cation positions, the non-metal elements randomly occupy the anion positions, and since the present invention adopts a composite target material spliced by disilicide and carbide, Si vacancies are introduced at the same time as C is introduced in the subsequent magnetron sputtering process, so that the high entropy silicon carbide anti-oxidation coating promotes the outward diffusion of silicon during the oxidation process, and quickly forms a dense and continuous SiO2 oxide layer on the surface, effectively restricting the inward diffusion of oxygen, and improving the oxidation resistance of the high entropy silicon carbide. At the same time, the high mixing entropy enhances the thermal stability of the high entropy silicon carbide anti-oxidation coating, which is beneficial for its long-term service at high temperatures. In addition, the present invention further improves the hardness and low-temperature toughness of the high entropy silicon carbide through carbon alloying.
[0024] The present invention also provides a method for preparing the high entropy silicon carbide described in the above technical scheme. The target material described in the present invention includes a mixture of TiSi2, ZrSi2, NbSi2, MoSi2, WSi2, WC and NbC. The high entropy silicon carbide anti-oxidation coating is regulated by selecting multiple elements, thereby reducing the difficulty of preparing the multi-component target material, being able to conveniently and quickly adjust the component composition of the high entropy silicon carbide, and the preparation method is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 A schematic diagram of the installation of a magnetron sputtering target for preparing a high entropy silicon carbide anti-oxidation coating according to the present invention;
[0027] Figure 2 Surface EDS images of the low-carbon-content high-entropy silicon carbide anti-oxidation coating of Example 1 and the high-carbon-content high-entropy silicon carbide anti-oxidation coating of Example 2 of the present invention;
[0028] Figure 3 The SEM cross-sectional images of the comparative example 1 Ti3Al, the comparative example 2 high entropy silicide coating, the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1 and the high carbon content high entropy silicon carbide anti-oxidation coating of Example 2 of the present invention after being oxidized in air at 800°C for 8h;
[0029] Figure 4 The SEM surface images of the comparative example 1 Ti3Al, the comparative example 2 high entropy silicide anti-oxidation coating, the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1 and the high carbon content high entropy silicon carbide anti-oxidation coating of Example 2 of the present invention;
[0030] Figure 5 The hardness diagram and micron indentation SEM diagram of the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1 of the present invention and the high entropy silicide anti-oxidation coating of Comparative Example 2 are shown. DETAILED DESCRIPTION
[0031] The present invention provides a high entropy silicon carbide anti-oxidation coating, comprising metal elements and non-metal elements, wherein the metal elements include Ti, Zr, Nb, Mo and W, and the non-metal elements include Si and C;
[0032] The molar ratio of metal elements to non-metal elements is 1:1.5-2;
[0033] The molar ratio of Ti, Zr, Nb, Mo and W is 1-10:1-10:1-10:1-10:1-10;
[0034] The carbon atom content is 10-40% of the total number of high entropy silicon carbide atoms.
[0035] In the present invention, the molar ratio of metal elements to non-metal elements is 1:1.5-2, and in a specific embodiment, it can be 1:2; the molar ratio of Ti, Zr, Nb, Mo and W is 1-10:1-10:1-10:1-10:1-10, and in a specific embodiment, it can be 3:4:7:8:5; the carbon atom content is 10-40% of the total number of high entropy silicon carbide atoms, and in a specific embodiment, it can be 17% or 38%.
[0036] In the present invention, the molar ratio of Si to C is 3:1-4.
[0037] In the present invention, the thickness of the high entropy silicon carbide anti-oxidation coating is 2-5 μm, and in a specific embodiment, it can be 3 μm or 4 μm.
[0038] The present invention also provides a method for preparing the high entropy silicon carbide anti-oxidation coating according to the above technical solution, comprising the following steps:
[0039] The target material is deposited on the surface of the substrate by magnetron sputtering to obtain the high entropy silicon carbide anti-oxidation coating on the surface of the substrate; the target material includes a mixture of TiSi2, ZrSi2, NbSi2, MoSi2, WSi2, WC and NbC.
[0040] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0041] In the present invention, the substrate comprises a Ti3Al sheet or a Ti3Al-based composite material fastener; the Ti3Al-based composite material fastener comprises SiC f reinforcement and Ti3Al matrix.
[0042] In the present invention, the substrate is polished and cleaned in sequence before use; the mesh number of the sandpaper used for polishing is 1000-7000 mesh, and in a specific embodiment, it can be 3000 mesh or 5000 mesh; the cleaning includes a first cleaning and a second cleaning; the first cleaning includes cleaning with acetone, ethanol and deionized water in sequence; the first cleaning method is ultrasonic, and the cleaning time of acetone, ethanol and deionized water in the second cleaning is independently 20-40 minutes; the second cleaning includes acid cleaning and deionized water cleaning in sequence; the reagent used for acid cleaning is HF solution; the concentration of the HF solution is 0.5-1wt%, and the acid cleaning time is 30-60s; the cleaning time of deionized water in the second cleaning is 20-40 minutes.
[0043] In the present invention, each target material is a strip target with a size of 10 to 150 mm*75 mm*8 mm. In a specific embodiment, it can be 10 mm*75 mm*8 mm.
[0044] In the present invention, the target material installation method includes: stacking and arranging from top to bottom in the vertical direction to form a first composite target and a second composite target; the arrangement order of the first composite target is TiSi2, ZrSi2, NbSi2, MoSi2 and WC, and the arrangement order of the second composite target is WC, MoSi2, NbSi2, ZrSi2 and TiSi2; or the arrangement order of the first composite target is TiSi2, ZrSi2, NbC, MoSi2 and WC, and the arrangement order of the second composite target is WC, MoSi2, NbC, ZrSi2 and TiSi2; the first composite target and the second composite target are arranged relative to each other; the arrangement period of the first composite target and the second composite target is independently 1 to 3, and in a specific embodiment, it can be 1, 2 or 3.
[0045] In the present invention, in addition to the above-mentioned TiSi2, ZrSi2, NbSi2, MoSi2, WSi2, WC and NbC targets, other transition metal silicide and carbide targets can also be selected for splicing.
[0046] In the present invention, the parameters of the magnetron sputtering include: the target sputtering current is 500-900 mA, in a specific embodiment, it can be 695 mA, 707 mA or 709 mA; the sputtering voltage value is 400-600 V; in a specific embodiment, it can be 495 V, 500 V or 550 V; the substrate bias is 0-200 V, in a specific embodiment, it can be 100 V or 150 V; the sample holder rotation speed is 100-200 r / h, in a specific embodiment, it can be 150 r / h or 180 r / h; the back pressure is less than 4×10 -4 Pa; the working pressure is 0.5-1.1Pa, and in a specific embodiment, it can be 0.8Pa, 0.9Pa or 1.0Pa; the substrate temperature is 300-500°C, and in a specific embodiment, it can be 350°C, 400°C or 450°C; the sputtering time is 40-80min, and in a specific embodiment, it can be 60min or 70min; the target-substrate distance is 6-10cm, and in a specific embodiment, it can be 7cm or 8cm; the magnetron sputtering is carried out in an argon atmosphere; the gas flow value of the argon is 50-70sccm, and in a specific embodiment, it can be 60sccm.
[0047] In an embodiment of the present invention, the operation steps of the magnetron sputtering include: closing the vacuum chamber door, evacuating the vacuum chamber to a pressure less than 4×10 -4Pa; turn on the heating power supply to raise the temperature to 300-500°C, open the gas circuit valve, introduce argon, set the argon gas flow value to 50-70sccm, adjust the gate valve to make the working pressure in the vacuum coating chamber 0.5-1.1Pa, adjust the substrate rack rotation speed to 150-250r / h, turn on the ion source power supply, and sputter and clean for 20-40min. After the ion source is cleaned, adjust the argon gas flow value back to 50-70sccm, adjust the gate valve to make the working pressure in the vacuum coating chamber 0.5-1.1Pa; adjust the target material sputtering current to 600-800mA, the sputtering voltage value to 400-600V, the substrate bias value to -50--200V, and sputter for 40-80min; after the deposition is completed, turn off the composite target sputtering power supply, stop introducing argon, adjust the gate valve to the maximum, and when the temperature in the vacuum chamber drops to room temperature, the high entropy silicon carbide anti-oxidation coating is obtained on the substrate surface;.
[0048] The present invention also provides a high entropy silicon carbide anti-oxidation coating for a Ti3Al-based composite material fastener, characterized in that it comprises a Ti3Al-based composite material fastener and a high entropy silicon carbide anti-oxidation coating deposited on the surface of the Ti3Al-based composite material fastener;
[0049] The high entropy silicon carbide anti-oxidation coating is the high entropy silicon carbide anti-oxidation coating described in the above technical solution or the high entropy silicon carbide anti-oxidation coating prepared by the preparation method described in the above technical solution.
[0050] The high entropy silicon carbide anti-oxidation coating of the Ti3Al-based composite material fastener of the present invention can be applied to the field of aerospace.
[0051] In order to further illustrate the present invention, a high entropy silicon carbide anti-oxidation coating of a Ti3Al-based composite fastener and a preparation method thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0052] Example 1
[0053] The Ti3Al composite fasteners were polished in a metal polishing machine with 1000 mesh, 3000 mesh, 5000 mesh and 7000 mesh sandpapers in turn until the surface was smooth without obvious scratches, and the polished Ti3Al sheets were placed in acetone, ethanol and deionized water for ultrasonic treatment for 20 minutes in turn, then pickled with 1% HF solution for 30 seconds, and then ultrasonically cleaned with deionized water for 20 minutes, and dried to obtain pretreated Ti3Al composite fasteners;
[0054] The pretreated Ti3Al composite fasteners were fixed on a rectangular sample holder and placed in the sample chamber of a multi-target magnetron sputtering device. TiSi2, ZrSi2, NbSi2, MoSi2, and WC strip targets with sizes of 10 mm*75 mm*8 mm were stacked in sequence from top to bottom in three cycles in the vertical direction and installed at target position A. WC, MoSi2, NbSi2, ZrSi2, and WC were stacked in the opposite order in the vertical direction. i2 , TiSi2 is arranged in 3 cycles and installed at the relative B target position. The installation position is as follows Figure 1 As shown, adjust the target-substrate distance to 10 cm; after preparation, close the vacuum chamber door and evacuate to less than 4×10 -4 Pa, when the vacuum degree reaches the requirement, turn on the heating power supply to raise the temperature to 500℃, open the gas circuit valve, introduce argon, set the argon gas flow value to 60sccm, adjust the gate valve to make the working pressure in the vacuum coating chamber to 0.8Pa, adjust the substrate rack rotation speed to 200r / h, turn on the ion source power supply, and sputter and clean for 20min. After the ion source is cleaned, adjust the argon gas flow value back to 60sccm, adjust the gate valve to make the working pressure in the vacuum coating chamber to 0.8Pa, turn on the sputtering power supply, adjust the composite target current value to 707mA, the sputtering voltage value to 500V, the substrate bias value to -100V, and sputter for 60min. After the deposition is completed, turn off the composite target sputtering power supply, close the gas circuit valve, and when the temperature in the vacuum chamber drops to room temperature, take out the sample, and obtain a low-carbon content high-entropy silicon carbide anti-oxidation coating on the Ti3Al composite fastener.
[0055] Example 2
[0056] The Ti3Al sheet was polished in a metal polishing machine with 1000 mesh, 3000 mesh, 5000 mesh and 7000 mesh sandpaper in sequence until the surface was smooth without obvious scratches. The polished Ti3Al sheet was placed in acetone, ethanol and deionized water for ultrasonic treatment for 20 minutes in sequence, then pickled with 1% HF solution for 30 seconds, and then ultrasonically cleaned with deionized water for 20 minutes, and dried to obtain a pretreated Ti3Al sheet;
[0057] The pretreated Ti3Al sheet was fixed on a rectangular sample holder and placed in the sample chamber of the multi-target magnetron sputtering equipment. TiSi2, ZrSi2, NbC, MoSi2, and WC strip targets of size 10mm*75mm*8mm were stacked in sequence from top to bottom in the vertical direction for 3 cycles and installed at the target position A. WC, MoSi2, NbC, ZrSi2, and TiSi2 were arranged in the opposite order in the vertical direction for 3 cycles and installed at the opposite target position B. The installation positions are as shown in the figure. Figure 1 As shown, adjust the target-substrate distance to 10 cm; after preparation, close the vacuum chamber door and evacuate to less than 4×10 -4Pa, when the vacuum degree reaches the requirement, turn on the heating power supply and raise the temperature to 500℃, open the gas circuit valve, introduce argon, set the argon gas flow value to 60sccm, adjust the gate valve so that the working pressure in the vacuum coating chamber is 0.8Pa, adjust the substrate rack rotation speed to 200r / h, turn on the ion source power supply, and sputter and clean for 20min. After the ion source is cleaned, adjust the argon gas flow value back to 60sccm, adjust the gate valve so that the working pressure in the vacuum coating chamber is 0.8Pa, turn on the sputtering power supply, adjust the composite target current value to 709mA, the sputtering voltage value to 495V, and sputter for 60min. After the deposition is completed, turn off the composite target sputtering power supply, close the gas circuit valve, and when the temperature in the vacuum chamber drops to room temperature, take out the sample, and obtain a high-carbon content and high-entropy silicon carbide anti-oxidation coating on the surface of the Ti3Al sheet.
[0058] Comparative Example 1
[0059] The Ti3Al sheet was polished in turn with 1000 mesh, 3000 mesh, 5000 mesh, and 7000 mesh sandpaper in a metal polishing machine until the surface was smooth without obvious scratches. The polished Ti3Al sheet was placed in acetone, ethanol, and deionized water for ultrasonic treatment for 20 minutes, then pickled with 1% HF solution for 30 seconds, and then ultrasonically cleaned with deionized water for 20 minutes and dried to obtain a pretreated Ti3Al sheet.
[0060] Comparative Example 2
[0061] The Ti3Al sheet was polished in a metal polishing machine with 1000 mesh, 3000 mesh, 5000 mesh, and 7000 mesh sandpaper in sequence until the surface was smooth without obvious scratches. The polished Ti3Al sheet was placed in acetone, ethanol, and deionized water for ultrasonic treatment for 20 minutes in sequence, then pickled with 1% HF solution for 30 seconds, and then ultrasonically cleaned with deionized water for 20 minutes, and dried to obtain a pretreated Ti3Al sheet;
[0062] The pretreated Ti3Al sheet was fixed on a rectangular sample holder and placed in the sample chamber of a multi-target magnetron sputtering device. TiSi2, ZrSi2, NbSi2, MoSi2, and WSi2 strip targets of size 10 mm*75 mm*8 mm were stacked in sequence from top to bottom in three cycles in the vertical direction and installed at the target position A. WSi2, MoSi2, NbSi2, ZrSi2, and TiSi2 were arranged in three cycles in the vertical direction in the opposite order and installed at the opposite target position B. The installation positions are as shown in FIG. Figure 1 As shown, adjust the target-substrate distance to 10 cm.
[0063] After the preparation is completed, close the vacuum chamber door and evacuate the vacuum chamber to a vacuum degree of less than 4×10 -4Pa; when the vacuum degree reaches the requirement, turn on the heating power supply and raise the temperature to 500℃, open the gas circuit valve, introduce argon, set the argon gas flow value to 60sccm, adjust the gate valve so that the working pressure in the vacuum coating chamber is 0.8Pa, adjust the substrate rack rotation speed to 200r / h, turn on the ion source power supply, and sputter and clean for 20min. After the ion source is cleaned, adjust the argon gas flow value back to 60sccm, adjust the gate valve so that the working pressure in the vacuum coating chamber is 0.8Pa. Adjust the composite target sputtering current to 695mA, the sputtering voltage value to 503V, the substrate bias value to -100V, and sputter for 60min. After the deposition is completed, turn off the composite target sputtering power supply, stop introducing argon, adjust the gate valve to the maximum, and when the temperature in the vacuum chamber drops to room temperature, take out the sample to obtain a high entropy silicide anti-oxidation coating on the surface of the Ti3Al sheet.
[0064] Test Case
[0065] A high temperature oxidation experiment was conducted on the pretreated Ti3Al sheets and the Ti3Al-based composite fastener / Ti3Al sheet samples deposited with high entropy silicon carbide anti-oxidation coating prepared in Examples 1 and 2 and Comparative Examples 1 and 2. The specific steps are as follows:
[0066] The above sample was placed in a crucible and placed in a tube furnace. An alumina insulation plug was placed at the seal, the flange was fastened, and the tail end was connected to the air. The tube furnace temperature program was adjusted to increase the temperature from room temperature to 800°C at a rate of 10°C / min and kept at this temperature for 8 hours to simulate the conditions of oxidation in the air. After the oxidation was completed, the power of the tube furnace was turned off, and the sample was cooled to room temperature with the furnace and tested. The results are shown below.
[0067] Figure 2 Surface EDS images of the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1 and the high carbon content high entropy silicon carbide anti-oxidation coating of Example 2 of the present invention, wherein (a) and (b) are surface EDS images of the high entropy silicon carbide anti-oxidation coating of Example 1 and Example 2, respectively. Figure 2 It can be seen that the present invention successfully prepared a multi-component high-entropy silicon carbide anti-oxidation coating.
[0068] Figure 3 The SEM cross-sectional images of the comparative example 1 Ti3Al, the comparative example 2 high entropy silicide coating, the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1 and the high carbon content high entropy silicon carbide anti-oxidation coating of Example 2 of the present invention after being oxidized in air at 800°C for 8h; Figure 4 The SEM surface images of the comparative example 1 Ti3Al, the comparative example 2 high entropy silicide anti-oxidation coating, the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1 and the high carbon content high entropy silicon carbide anti-oxidation coating of Example 2 of the present invention; Figure 3 and Figure 4(a) is the cross-sectional and surface SEM image of Ti3Al of comparative example 1, (b) is the cross-sectional and surface SEM image of high entropy silicide anti-oxidation coating of comparative example 2, (c) is the cross-sectional and surface SEM image of high entropy silicon carbide anti-oxidation coating of low carbon content of embodiment 1, and (d) is the cross-sectional and surface SEM image of high entropy silicon carbide anti-oxidation coating of high carbon content of embodiment 2. Figures 3-4 It can be seen that the surface of the Ti3Al substrate that has only been pretreated is covered with a thick loose oxide layer, which is about 6.16μm thick and has a surface roughness of 105nm. A large number of holes appear on the oxidized surface, which indicates that the Ti3Al substrate undergoes severe oxidation at 800°C; the thickness of the low-carbon content high-entropy silicon carbide anti-oxidation coating in Comparative Example 2 is 596nm thick and 8.49nm roughness. The thickness of the oxide layer is significantly reduced compared with Comparative Example 1. This is because the silicon element in the high-entropy silicide anti-oxidation coating is preferentially oxidized to form a denser SiO2 layer, thereby hindering the further diffusion of oxygen; the oxide layer thickness of the low-carbon content high-entropy silicon carbide anti-oxidation coating in Example 1 is 474nm thick and the surface is rough The thickness of the oxide layer is 6.88nm, which is slightly reduced compared with that of Comparative Example 2, and the oxide layer is more uniform and dense; the thickness of the high-carbon content and high-entropy silicon carbide anti-oxidation coating in Example 2 is 615nm, and metal oxide particles are formed on the surface. The surface roughness is 37.8nm. As the carbon content further increases, the oxidation resistance of the high-entropy silicon carbide decreases. Therefore, in the high-entropy silicon carbide anti-oxidation coating, a small amount of carbon atoms with strong affinity for metal elements and silicon vacancies introduced at the anion position promote the diffusion of silicon to the surface, inhibit the formation of metal oxides, and quickly form a continuous and dense SiO2 layer in the early stage of oxidation, which hinders the further diffusion of oxygen inward, thereby improving the oxidation resistance to a certain extent.
[0069] Figure 5 The hardness diagram and micron indentation SEM diagram of the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1 of the present invention and the high entropy silicide anti-oxidation coating of Comparative Example 2 are shown, wherein (a) is the hardness diagram of the high entropy silicon carbide anti-oxidation coating of Example 1 and the high entropy silicide anti-oxidation coating of Comparative Example 2, (b) is the SEM diagram of the high entropy silicide anti-oxidation coating of Comparative Example 2, and (c) is the SEM diagram of the low carbon content high entropy silicon carbide anti-oxidation coating of Example 1. Figure 5It can be seen that the high entropy silicon carbide anti-oxidation coating obtained in this embodiment is subjected to hardness testing and SEM characterization at the micron indentation. As shown in (a), the hardness of the high entropy silicide anti-oxidation coating of Comparative Example 2 is 19.5GPa; the modulus is 156.2Gpa. From the micron indentation SEM image (b), more obvious cracks begin to appear in Comparative Example 2. This is due to the high content of Si-Si bonds in the high entropy silicide, which causes the coating to be more brittle; the hardness of the low-carbon high entropy silicon carbide anti-oxidation coating obtained in Example 1 of the present invention is 24GPa, and the modulus is 212.51Gpa. From the indentation SEM image (c), the high entropy silicon carbide anti-oxidation coating of Example 1 of the present invention is almost free of cracks, which indicates that the hardness and toughness of the high entropy silicon carbide anti-oxidation coating are improved compared with the corresponding high entropy silicide anti-oxidation coating.
[0070] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A high entropy silicon carbide anti-oxidation coating, characterized in that: Includes metal elements and non-metal elements, the metal elements include Ti, Zr, Nb, Mo and W, and the non-metal elements include Si and C; The molar ratio of metal elements to non-metal elements is 1:1.5-2; The molar ratio of Ti, Zr, Nb, Mo and W is 1-10:1-10:1-10:1-10:1-10; The carbon atom content is 10-40% of the total number of high entropy silicon carbide atoms.
2. The high entropy silicon carbide anti-oxidation coating according to claim 1, characterized in that: The molar ratio of Si to C is 3:1-4.
3. The high entropy silicon carbide anti-oxidation coating according to claim 1, characterized in that: The thickness of the high entropy silicon carbide anti-oxidation coating is 2-5 μm.
4. The method for preparing the high entropy silicon carbide anti-oxidation coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: The target material is deposited on the surface of the substrate by magnetron sputtering to obtain the high entropy silicon carbide anti-oxidation coating on the surface of the substrate; the target material includes a mixture of TiSi2, ZrSi2, NbSi2, MoSi2, WSi2, WC and NbC.
5. The preparation method according to claim 4, characterized in that: The substrate includes a Ti3Al sheet or a Ti3Al-based composite material fastener.
6. The preparation method according to claim 4 or 5, characterized in that: The target material installation method comprises: stacking and arranging from top to bottom in a vertical direction to form a first composite target and a second composite target; the first composite target is arranged in the order of TiSi2, ZrSi2, NbSi2, MoSi2 and WC, and the second composite target is arranged in the order of WC, MoSi2, NbSi2, ZrSi2 and TiSi2; or the first composite targets are arranged in the order of TiSi2, ZrSi2, NbC, MoSi2 and WC, and the second composite targets are arranged in the order of WC, MoSi2, NbC, ZrSi2 and TiSi2; The first composite target and the second composite target are arranged opposite to each other; The arrangement period of the first composite target and the second composite target is independently 1 to 3.
7. The preparation method according to claim 4, characterized in that: The parameters of the magnetron sputtering include: the sputtering current of each target is 500-900 mA, the sputtering voltage value is 400-600 V, the substrate bias is -50--200 V, the sample holder speed is 150-250 r / h, the back pressure is less than 4×10 -4 Pa, the working pressure is 0.5-1.1 Pa, the substrate temperature is 300-500° C., the sputtering time is 40-80 min, and the target-substrate distance is 6-10 cm; the magnetron sputtering is carried out in an argon atmosphere; the gas flow value of the argon is 50-70 sccm.
8. The preparation method according to claim 4, characterized in that: The temperature of the substrate during the magnetron sputtering is 300-500°C.
9. A high entropy silicon carbide anti-oxidation coating for a Ti3Al-based composite fastener, characterized in that: It comprises a Ti3Al-based composite material fastener and a high entropy silicon carbide anti-oxidation coating deposited on the surface of the Ti3Al-based composite material fastener; The high entropy silicon carbide anti-oxidation coating is the high entropy silicon carbide anti-oxidation coating according to any one of claims 1 to 3 or the high entropy silicon carbide anti-oxidation coating prepared by the preparation method according to any one of claims 4 to 8.
Citation Information
Patent Citations
Sputtering target assembly
CN103380228A
Method for preparing photomask blank, photomask blank, method for preparing photomask, photomask and metallic chromium target
CN108415218A
Graphene toughened high-entropy silicide ceramic as well as preparation method and application thereof
CN112062576A
Low-density NbTiTaCrSiC series refractory high-entropy high-temperature alloy
CN116949339A
High-entropy carbon-nitrogen compound ceramic composite coating and preparation method thereof
CN117604446A